Syphilis in Pernambuco: an epidemiological analysis of the last five years (Research, Society and Development, 2023)
Objective: to analyze the epidemiological history of syphilis acquired in the last five years in Pernambuco. Methodology: ecological, retrospective, descriptive epidemiological study with a quantitative approach, listing the relevant numbers needed to investigate the behavior of acquired syphilis in the state of Pernambuco. Results: In the period from 2017 to 2021, 30,594 were notified, of this total, individuals aged 20 to 29 years accounted for 35.2% of cases, males exceeded the number of cases of syphilis acquired in all years, except, in 2017. The disease is mainly distributed among people aged 20 to 29 years old, mixed race and the white ones, male and also in the group of those who completed high school. Conclusion: the time series showed that there was an increase in cases over the years, as well as an increasing trend in acquired syphilis, even though COVID-19 had an impact on the 2020 data. Health actions must continue to improve access to diagnosis and notification, with a focus on treatment, cure and health education actions, to control and prevent new cases even in municipalities with a high human development index.